2023
DOI: 10.1038/s41559-023-02044-6
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell adaptations shape evolutionary transitions to multicellularity in green algae

Abstract: The evolution of multicellular life has played a pivotal role in shaping biological diversity. However, we know surprisingly little about the natural environmental conditions that favour the formation of multicellular groups. Here we experimentally examine how key environmental factors (predation, nitrogen and water turbulence) combine to influence multicellular group formation in 35 wild unicellular green algae strains (19 Chlorophyta species). All environmental factors induced the formation of multicellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 95 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…We know surprisingly little about the natural environmental conditions that favor the formation of multicellular groups. Adaptations of unicellular organisms to environmental challenges may hold the key to understanding evolutionary pathways to multicellular life [48]. TEM of the microalgal samples provided us the confirmation that the isolated endosymbiotic microalgae may be the base for the microalgal net formation.…”
Section: Discussionmentioning
confidence: 89%
“…We know surprisingly little about the natural environmental conditions that favor the formation of multicellular groups. Adaptations of unicellular organisms to environmental challenges may hold the key to understanding evolutionary pathways to multicellular life [48]. TEM of the microalgal samples provided us the confirmation that the isolated endosymbiotic microalgae may be the base for the microalgal net formation.…”
Section: Discussionmentioning
confidence: 89%
“…According to Cornwallis et al , 40 multicellularity has allowed new levels of morphological complexity to develop, but it is still unclear what ecological advantages or benefits multicellularity provides. It has been suggested that possible benefits of forming multicellular groups as an adaptation are to protect unicellular organisms from various environmental stressors such as predation and toxins.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that possible benefits of forming multicellular groups as an adaptation are to protect unicellular organisms from various environmental stressors such as predation and toxins. 40,41 Earlier studies examining the costs and benefits of group formation in algae have produced mixed results. 41,42 According to Lürling et al, 42 multicelled colonies of algae have a higher sinking rate and lower ability to absorb nutrients compared to unicellular algae, but according to Cornwallis et al, 40 they can protect themselves from various stressors.…”
Section: Microalgae Growth Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used two protist predators of similar body size, Tetrahymena pyriformis and Glaucoma sp., as the focal predators, and a larger protist Paramecium caudatum, as a competitor for the predators (Fig 1b). All four species are commonly found in freshwater and soil systems (Cornwallis et al 2023;Foissner & Berger 1996).…”
Section: Experimental Workmentioning
confidence: 99%